2017
DOI: 10.3389/fnbeh.2017.00089
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ancestral Programming of Resilience in a Two-Hit Stress Model

Abstract: In a continuously stressful environment, the effects of recurrent prenatal stress (PS) may accumulate across generations and alter stress vulnerability and resilience. Here, we report in female rats that a family history of recurrent ancestral PS facilitates certain aspects of movement performance, and that these benefits are abolished by the experience of a second hit, induced by a silent ischemia during adulthood. Female F4-generation rats with and without a family history of cumulative multigenerational PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…The volume averages were calculated by dividing the sum of measures obtained from each brain by the total number of sections (shrunk brain area in mm 2 ). The approximate volume of the cortex and hippocampus (HPC; shrunk volume in mm 3 ) was determined by multiplying the total area in mm 2 by both the thickness of each slice (40 μm) and the sampling interval (5) 34 . The hippocampal volume (B6, n = 7; BTBR, n = 8) in each mouse was estimated using a set of four cross sections of the dHPC area, from ~−1.06 to ~−2.06 mm relative to bregma.…”
Section: Methodsmentioning
confidence: 99%
“…The volume averages were calculated by dividing the sum of measures obtained from each brain by the total number of sections (shrunk brain area in mm 2 ). The approximate volume of the cortex and hippocampus (HPC; shrunk volume in mm 3 ) was determined by multiplying the total area in mm 2 by both the thickness of each slice (40 μm) and the sampling interval (5) 34 . The hippocampal volume (B6, n = 7; BTBR, n = 8) in each mouse was estimated using a set of four cross sections of the dHPC area, from ~−1.06 to ~−2.06 mm relative to bregma.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies revealed that multigenerational prenatal stress (MPS) in particular is more potent in programming the stress response than early life stress [15,26], especially in male offspring. The recurrent gestational challenge in MPS models was shown to impair fine motor function, alter neuromorphology and induce hemispheric dominance shifts in males [3,16], while improving fine function and promoting resilience in females [17]. Thus, MPS models may offer unique insights into evolutionary mechanisms of sex-dependent adaptation and resilience.…”
Section: Agingmentioning
confidence: 99%
“…Thus, MPS models may offer unique insights into evolutionary mechanisms of sex-dependent adaptation and resilience. Research has shown that ancestral biological memories of adverse experiences are linked to epigenetic modification, such as DNA methylation [30,33,34], histone modification [35][36][37] and miRNA expression [17,26,[30][31][32]. Notably, the consequences of ancestral stress become particularly visible during early development and old age [16].…”
Section: Agingmentioning
confidence: 99%
See 2 more Smart Citations